Peran Permainan Edukatif dalam Pengembangan Kecerdasan Emosional Anak Usia Dini di TK Swasta Asmaul Husna Asahan - Ernawati, Edmi; Rahman, Mhd Habibu (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the role of educational games in developing emotional intelligence in early childhood at Asmaul Husna Private Kindergarten in Asahan. The research method used was descriptive qualitative, with data collected through observation, interviews, and documentation with teachers and children. The results indicate that educationally designed play activities can improve aspects of emotional intelligence, such as the ability to recognize emotions, manage feelings, show empathy, and build positive social interactions. Role-playing, group play, and creative exploration have proven effective as media for emotional learning. The teacher's role as a companion and facilitator is also crucial to the success of this process. Educational games play a crucial role in developing emotional intelligence in early childhood and should be an integral part of learning activities in early childhood education institutions.